Clinical efficacy and safety of acupuncture treatment of TIC disorder in children: A systematic review and meta-analysis of 22 randomized controlled trials - Chen Lu; Li-qun Wu; Hongwen Hao; Xinting Kimberly Leow; Fang-wei Xu; Pan-pan Li; Dong-sheng Wang (Elsevier, 2021)
Objective: To systematically evaluate the clinical efficacy and safety of acupuncture in the treatment of Tic Disorders (TD) in children, and to clarify the current evidence regarding the clinical application of acupuncture in the treatment of TD. Methods: Randomized controlled trials (RCTs) comparing acupuncture treatment with pharmaceutical treatment for TD were included in this review. A comprehensive search of 6 electronic literature databases was conducted, and the retrieval date was from the establishment of the database to April 2020. The Cochrane Collaboration's bias risk assessment tool was used to evaluate the bias risk of the included literature, and adopted the Review Manager 5.3 was used for statistical analysis of the data in the included literature. Results: A total of 22 RCTs (1668 participants) were included in this review. Meta-analysis indicated that acupuncture showed superior effects in the following aspects, including higher overall effective rate [RR = 1.20,95 % CI(1.09,1.20),P＜0.00001], significant reduction in Yale Global Tic Severity Scale (YGTSS) scores [MD=-2.79,95 %CI(-4.75,-0.82),P = 0.005], lower incidence of adverse effects [RR = 0.26,95 %CI(0.17,0.41),P＜0.00001], and reduced recurrence rate [RR = 0.28,95 %CI(0.17,0.46),P＜0.00001]. Conclusion: Acupuncture treatment alone is more effective in the treatment of TD than pharmaceutical treatment, as seen in the reduction of YGTSS scores, fewer adverse effects and lower recurrence rates.